A NEW PARADIGM OF INTEGRATION BETWEEN SCIENCE AND ISLAM: An Epistemological Framework - Tajuddin, Muhammad Saleh; Hj. Rofie, Mohamad Khadafi (Journal of Islam and Science, 2014)
This writing discusses about integration between science and Islam. The main purpose of the writing is to introduce a new paradigm of integration between science and Islam through some models, namely Islamization of science who is introduced by Ismail al-Furuqi and construct a paradigm of Islamic science who is introduced by Ziauddin Sardar. This writing is done by doing research in library and running qualitative research based on philosophical approach. The data is collected from books, journals, and the internet. The study is analyzed through descriptive analysis to get accurate results from the objective of the study. The epistemological theory that is used in this study is “construct of paradigm” theory of Thomas Kuhn to analyze the dichotomy of science and Islam and how to integrate them. The results of the research are: there are two models of integration between science and Islam, viz. Islamization of science and establish of Islamic science paradigm. The paradigms are very important to anticipate the universal problem of science.